Research and Evaluation of the Exeter Health Care Arts Project. Issue 2 (1st December 2000) - Scher, Peter; Senior, Peter
Abstract : An arts project was initiated at the newly rebuilt district hospital in the city of Exeter in south west England. This paper describes an independent research evaluation project covering the period from its inception in 1992. The findings include both qualitative and economic aspects and were compared with the authors' wider experience of similar projects. For the first time the responses of clinical staff about the effects of art on the healing process, on therapeutic benefit and on morale are independently assessed. The results provide data and new insights into the interactions of patients, staff and visitors with the arts in the hospital environment. The conclusions offer important guidance for other arts projects and for researchers to develop the methodology in further studies, providing feedback for clinical staff, designers, artists, managers, and policy makers.